Cefiderocol for the Treatment of Multidrug-Resistant Gram-Negative Bacteria: A Systematic Review of Currently Available Evidence - Wang, Chuanhai; Yang, Deqing; Wang, Yifan; Ni, Wentao (Frontiers in Pharmacology, 2022)
Cefiderocol is a novel synthetic siderophore-conjugated antibiotic that hijacks the bacterial iron transport systems facilitating drug entry into cells, achieving high periplasmic concentrations. This systematic review analyzed the currently available literature on cefiderocol. It summarized in vitro susceptibility data, in vivo antimicrobial activity, pharmacokinetics/pharmacodynamics (PK/PD), clinical efficacy, safety and resistance mechanisms of cefiderocol. Cefiderocol has potent in vitro and in vivo activity against multidrug-resistant (MDR) Gram-negative bacteria, including carbapenem-resistant isolates. But New Delhi Metallo-β-lactamase (NDM)- positive isolates showed significantly higher MICs than other carbapenemase-producing Enterobacterales, with a susceptible rate of 83.4% for cefiderocol. Cefiderocol is well-tolerated, and the PK/PD target values can be achieved using a standard dose regimen or adjusted doses according to renal function. Clinical trials demonstrated that cefiderocol was non-inferiority to the comparator drugs in treating complicated urinary tract infection and nosocomial pneumonia. Case reports and series showed that cefiderocol was a promising therapeutic agent in carbapenem-resistant infections. However, resistant isolates and reduced susceptibility during treatment to cefiderocol have already been reported. In conclusion, cefiderocol is a promising powerful weapon for treating MDR recalcitrant infections.